Erratum to: Electromagnetic dipole moments of charged baryons with bent crystals at the LHC - E. Bagli; L. Bandiera; G. Cavoto; V. Guidi; L. Henry; D. Marangotto; F. Martinez Vidal; A. Mazzolari; A. Merli; N. Neri; J. Ruiz Vidal; A. Sytov; et al. (European Physical Journal C: Particles and Fields, 2020)
In this Erratum, an improved simulation of the channeling efficiency of protons and antiprotons as a function of the particle momentum is shown in for different configurations